2006
DOI: 10.1177/070674370605100602
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Associations between Delusional Disorder and Paranoid Schizophrenia: A Novel Etiologic Approach

Abstract: Objectives: Genetic associations between delusional disorder and paranoid schizophrenia are not well understood, although involvement of biological factors has been suspected. We investigated the incidence of human leukocyte antigen (HLA) class I alleles in patients with delusional disorder and paranoid schizophrenia, first, to explore a possible immunogenetic etiology of these paranoid disorders and, second, to determine whether they share similar etiologic mechanisms. Method:We employed a nested case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…67 The authors of another study proposed that HLA-G antigens are pivotal in the development of schizophrenia. 68 Further positive statistical associations between particular HLA alleles and the development of schizophrenia have been found with HLA-A10*03, 69 HLA-DRB1, 70 and HLA-B15. 56 Negative associations have been found with HLA-B35, 56 HLA-DQB1, 71 and HLA-DQB1*0402.…”
Section: Genetic Susceptibilitymentioning
confidence: 96%
“…67 The authors of another study proposed that HLA-G antigens are pivotal in the development of schizophrenia. 68 Further positive statistical associations between particular HLA alleles and the development of schizophrenia have been found with HLA-A10*03, 69 HLA-DRB1, 70 and HLA-B15. 56 Negative associations have been found with HLA-B35, 56 HLA-DQB1, 71 and HLA-DQB1*0402.…”
Section: Genetic Susceptibilitymentioning
confidence: 96%
“…Morimoto et al [11] described dopamine system dysregulation in persecutory DD, as shown by elevated levels of plasma homovanillic acid and polymorphisms of dopaminergic receptor genes such as DRD2 and DRS 3. Furthermore, an association of HLA-A*03-Gen [19] has been found. In previous neuroimaging studies, structural and functional abnormalities in distinct frontotemporal regions, anterior cingulate cortex and insula were frequently observed [20,21].…”
Section: Introductionmentioning
confidence: 82%
“…The limited work on the diagnostic relationships of delusional disorder include a study of monozygotic/dizygotic concordance rates for schizophrenia spectrum disorders, which found that delusional disorder is unlikely to be related to them (Farmer 1987). This is supported by more recent genetic research evidence, which suggests that delusional disorder has no relation to the dopamine D 1 receptor gene (Debnath 2010). There is a school of thought that considers delusional disorder to relate more naturally to a currently disparate group of disorders that contain both obsessional and delusional components (Fear 2000;O'Dwyer 2000;see also Hollander (1993) and Hollander et al (2011) for detailed commentary).…”
Section: Declaration Of Interestmentioning
confidence: 99%